Plasmodium falciparum-infected erythrocyte knob density is linked to the PfEMP1 variant expressed - Barfod, L; Subramani, R; Quadt, K; Jeppesen, A; Hempel, C; Vang Petersen, J; Hassenkam, T; Hviid, L (American Society for Microbiology, 2015)
Members of the clonally variant Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) family mediate adhesion of infected erythrocytes (IEs) to vascular receptors. PfEMP1 expression is normally confined to nanoscale knob protrusions on the IE surface membrane. To investigate the relationship between the densities of these IE surface knobs and the PfEMP1 variant expressed, we used specific antibody panning to generate three sublines of the P. falciparum clone IT4, which expresses the PfEMP1 variants IT4VAR04, IT4VAR32b, and IT4VAR60. The knob density in each subline was then determined by atomic force microscopy (AFM) and scanning electron microscopy (SEM) and compared to PfEMP1 and knob-associated histidine-rich protein (KAHRP) expression. Selection for uniform expression of IT4VAR04 produced little change in knob density, compared to unselected IEs. In contrast, selection for IT4VAR32b expression increased knob density approximately 3-fold, whereas IEs selected for IT4VAR60 expression were essentially knobless. When IT4VAR60+ IEs were subsequently selected to express IT4VAR04 or IT4VAR32b, they again displayed low and high knob densities, respectively. All sublines expressed KAHRP regardless of the PfEMP1 expressed. Our study documents for the first time that knob density is related to the PfEMP1 variant expressed. This may reflect topological requirements to ensure optimal adhesive properties of the IEs.